2021
DOI: 10.1080/21655979.2021.1995579
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA SNHG8 accelerates acute gouty arthritis development by upregulating AP3D1 in mice

Abstract: Gout can affect the quality of life of patients due to monosodium urate monohydrate (MSU) crystals. Numerous studies have proposed that long noncoding RNAs (lncRNAs) regulate gout. We aimed to reveal the function of lncRNA small nucleolar RNA host gene 8 (SNHG8) in acute gouty arthritis (GA). A GA mouse model was established by injection of MSU into footpads. The levels of SNHG8, miR-542-3p and adaptor-related protein complex 3 subunit delta 1 (AP3D1) in footpads were detected via polymerase chain reaction ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In addition to IL-1β, two other pro-inflammatory cytokines, IL-6 and TNF-α, have been commonly used to assess the therapeutic effects. 44,45 In line with previous studies, 44,45 their levels were found to be increased in the G-PS mice compared to the NC group (Fig. 6C and D).…”
Section: Resultssupporting
confidence: 92%
“…In addition to IL-1β, two other pro-inflammatory cytokines, IL-6 and TNF-α, have been commonly used to assess the therapeutic effects. 44,45 In line with previous studies, 44,45 their levels were found to be increased in the G-PS mice compared to the NC group (Fig. 6C and D).…”
Section: Resultssupporting
confidence: 92%
“…As a non‐coding RNA, multiple lncRNAs have been identified in AGA in recent years. For example, SNHG8 was aberrantly increased in AGA and promoted mouse AGA progression by regulating miR‐542‐3p/AP3D1 5 . lncRNA‐MM2P is abnormally reduced in MSU‐treated macrophages and participates in the inflammation by regulating macrophage polarization 7 .…”
Section: Discussionmentioning
confidence: 99%
“…They exert regulatory effects on gene levels and function via the transcriptional level, post‐transcriptional level (affecting protein translation, synthesis, and degradation), and epigenetic level (DNA methylation, acetylation). lncRNAs are emerging as novel biomarkers for disease diagnosis and treatment, and regulating them is a powerful strategy to stop disease progressions, such as SNHG8, 5 H19, 6 and lncRNA‐MM2P 7 . lncRNA HOXA distal transcript antisense RNA (HOTTIP) is located on chromosome 7p15.2.…”
Section: Introductionmentioning
confidence: 99%
“…Gout is a metabolic disease and a common cause of inflammatory arthritis [ 1 , 2 ]. Epidemiological studies show that the prevalence of gout is 0.6% in developed and 1.1% in China [ 3 , 4 ]. The prevalence is 1.5% among men and 0.9% for women [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show that the prevalence of gout is 0.6% in developed and 1.1% in China [ 3 , 4 ]. The prevalence is 1.5% among men and 0.9% for women [ 4 ]. Disorders of the purine catabolic pathway cause hyperuricemia wherein serum urate levels consistently exceed in limit of 7.0 mg/dL [ 2 ].…”
Section: Introductionmentioning
confidence: 99%